PERAN KOMUNITAS KERAJINAN DAUR ULANG SAMPAH (KerDUS) SEBAGAI PROMOTOR EDUKASI ZERO WASTE DI KABUPATEN KENDAL - Yeni Selfia; Nanik Hidayati; Abdul Majid (Dialogue : Jurnal Ilmu Administrasi Publik, 2020)
The problem of waste nowadays is not merely on the various type always increasing waste, but more importantly is how to break the potential waste chain from its source. Therefore  gradual and continuous education on  the importance of reducing or eliminating waste is of importance. The KerDUS community, which is one of the volunteer communities of environmental conservation in Kendal Regency, provides education to the public on the importance of clean living without making waste. The purpose of this study is to determine the role of the KerDUS Community in the success of waste education in the Kendal Regency. This study use qualitative descriptive method that describes the role and activities of the KerDUS Community in providing zero-waste education in the Kendal Regency. Data from observations, interviews, documentation, and questionnaires were collected to be analyzed with the stages of data reduction, data presentation, before drawing conclusions. The results of the study show that the KerDUS community has an important role as a motivator for education towards zero waste in Kendal in the form of workshops or routine monthly training, besides education through Islamic groups in all levels of society. The KerDUS community also sends its members to attend trainer of training or the like to improve the members’ abilities and creativity. Various educational activities are also carried out such as the manufacturing of liquid organic fertilizer, eco brick, paragon pipe decorative lights, various plastic crackle flowers, and various coffee packaging creations. It is hoped that the small KerDUS community can provide a change to the zero-waste lifestyle not only to the people in Kendal Regency but also for a wider society in other regions with the support of relevant agencies and the government.